Code Switching In Twitter Of Alexander Thian: A Synactic Analysis - Silalahi, Gabriella Mauretania; Tetty, Morada (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This thesis analyses the types, the use, and the reason why Code-switching are used in Alexander Thian on his tweets. This study used Poplack and Hoffman™s theory in order to answer the problems and used a descriptive qualitative method to analyze. There are three types in Poplack Theory and seven reasons why code-switching used in Hoffman Theory. The source of data is Twitter and there are 50 tweets found as the data. Those tweets in Alexander Thian™s twitter were examined to categorize them into distinct categories. This study found that Alexander Thian uses three types of code-switching in his twitter account, namely tag-switching (4%), inter-sentential switching (42%), and intra-sentential switching (54%).  While for the reasons, the Code switching were mostly used in talking about particular topic twenty-six tweets (52%), quoting somebody else six tweets (12%), being emphatic about something ten tweets (20%), interjection four tweets (8%), intention of clarifying the speech content two tweets (4%), and expressing group identity two tweets (4%).